Calculation of the plastic metal flow in the cold extrusion technology by finite volume method - Bašić, Hazim (Array, 2020)
This paper presents an application of the finite volume method to ideal plastic metal flow in extrusion technology. Governing equations for the mass and momentum balance are used in an integral form. Solution domains in the cases considered are discretized with a Cartesian numerical mesh with computational points placed at the center of each control volume. After discretization of the governing equations, the resulting system of nonlinear algebraic equations is solved by an iterative procedure, using a segregated algorithm approach. Resulting stress fields are obtained from the Levy-Mises equations. The experimental results and numerical calculations are in good agreement.